Generation of double-exponential EMC pulses with Software-Defined Radios - Perotoni, M. B.; Vieira, M. S.; Santos, K. M. (Advanced Electromagnetics, 2022)
This article presents a system to generate transient signals for EMC testing purposes. It is based on a low-cost commercial Software-Defined Radio (SDR) whose output contains the desired transient signal modulated by a higher-frequency sinusoidal. An envelope detector board removes the carrier so that the slow-varying curve is amplified to be used in the test setup. Due to the SDR nature, it is completely controlled by software, which enables a quick and easy operation able to synthesize different waveforms. An open-source software tool is used to control the SDR to generate the signal and set the carrier frequency. Here, the article focuses on double-exponential curves, very common in different EMC tests, but its application is not limited to them. A 5.9 s risetime waveform is generated and tested against a real prototype representing a shielded cable over a ground plane. Individual building blocks are presented and the signal is analyzed as it goes through the cascade.